2005
DOI: 10.4049/jimmunol.175.8.5498
|View full text |Cite
|
Sign up to set email alerts
|

Defined Blocks in Terminal Plasma Cell Differentiation of Common Variable Immunodeficiency Patients

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous disorder characterized by defective Ab production and recurrent bacterial infections. The largely unknown causes are likely to comprise a diverse set of genetic or acquired defects. In this study, we investigated terminal B cell differentiation in lymph nodes from CVID patients. Up to the germinal center B cell stage, B cell differentiation was normal but terminal plasma cell development was found to be impaired. Using differential Blimp-1 and Syndecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 37 publications
0
30
0
3
Order By: Relevance
“…Such cells could alternatively arise through escape from the GC after initiation of proliferation at the centroblast state prior to the initiation of SHM. Although far from definitive evidence exists for this latter possibility, a small study of biopsied lymph nodes from three subjects with CVID found evidence of centroblasts but a lack of centrocytes, consistent with successful expansion of pre-mutated B cell populations in CVID (56). Increased B cell clonality is expected in patients who develop B cell lymphomas.…”
Section: Discussionmentioning
confidence: 97%
“…Such cells could alternatively arise through escape from the GC after initiation of proliferation at the centroblast state prior to the initiation of SHM. Although far from definitive evidence exists for this latter possibility, a small study of biopsied lymph nodes from three subjects with CVID found evidence of centroblasts but a lack of centrocytes, consistent with successful expansion of pre-mutated B cell populations in CVID (56). Increased B cell clonality is expected in patients who develop B cell lymphomas.…”
Section: Discussionmentioning
confidence: 97%
“…The cellular studies of the immune system in CVID subjects to date have shown numerical and functional defects in B, T, natural killer cells, macrophages and monocytes [3944]. T cell functional abnormalities are common (20% of CVID subjects) [4,45] with defects in cytokine production, T helper function, and T cell signaling [19,4652].…”
Section: Discussionmentioning
confidence: 99%
“…Mice that are CD86 deficient fail to respond to antigen challenge, lacking antibody formation and isotype switching, congruent with defects seen in CVID [8,9]. CVID B cells exhibit increased apoptosis, presumably due to increased expression of CD95 (Fas) and reduced expression of CD38 [1012]. With enhanced apoptosis, B cells could be unable to complete the maturation and differentiation process needed for B-cell development.…”
Section: Cvid B-cell Defects and Classification Schemesmentioning
confidence: 97%